ANTI-INFLAMMATORY ACTIVITIES OF PEPEROMIA PELLUCIDA [L.] KUNTH.: A REVIEW - I Gusti Agung Ayu Kartika; Ni Ketut Sinarsih; Ni Made Dwi Mara Widyani Nayaka (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2022)
Background: Inflammation is a natural body response, but when it reaches the systemic chronic inflammation stage, it can cause more dangerous complications. Many natural ingredients have been developed as anti-inflammatory agents. One of them is sirih bumi (Peperomia pellucida [L.] Kunth). Objective: This study aims to summarize and examine the research results related to the anti-inflammatory activity of the sirih bumi. Methods: Research articles were collected from various online databases such as Google Scholar, Google, Medline, Pubmed, and Science Direct. Inclusion and exclusion criteria were applied to obtain original research articles relevant to the desired topic, published in the last ten years, the full text was accessible, and the research methods and results were well explained and valid. Results: In total, only six articles are eligible to be discussed. The research was conducted in Indonesia, Nigeria, and Malaysia. In vitro and in vivo methods with various models and parameters were used to test the anti-inflammatory activity. All parts of the plant are proven to have anti-inflammatory effects that can be presented in extracts or herbal teas. The activity of sirih bumi is determined by the dose or concentration of administration, processing process, and harvest time. The combination with other samples must be reconsidered to maintain the desired anti-inflammatory effect. Conclusion: Antiinflammatory activity of sirih bumi has been proven through various studies. The development of the sirih bumi product is expected to help handle inflammation and other diseases related to inflammation. Keywords: peperomia pellucida; inflammation; extract; tea